Front-crawl stroke descriptors variability assessment for skill characterisation? - Dadashi, F.; Millet, G. P.; Aminian, K. (Journal of Sports Sciences, 2016)
The goal of this article is to characterise front-crawl swimming skill based on variability pattern of technique descriptors. Nine national level and nine recreational swimmers performed three 300 m trials in a 50 m outdoor pool, at 70%, 80% and 90% of their front-crawl 400 m personal best time. Using wearable inertial measurement units (IMUs) and validated algorithms we assessed the variability of technique descriptors at each arm cycle (139 ± 17 per trial). We calculated the duration of pull, push and non-propulsive phases, index of coordination (IdC), stroke length, stroke rate and intra-cyclic velocity variation. To track intra-trial technique variability, we calculated the Cauchy index to quantify the stability of multidimensional technique descriptors in space-time. Skilled swimmers, having access to divers motor solutions, achieved significantly higher velocities at similar intensities and similar IdC (P < 0.01) with more stable motor pattern (smaller Cauchy index). Besides, the similarity of intra-cyclic velocity variation at different intensities denotes that skilled swimmers used a wider dynamic range of velocity. We also introduced cycle velocity variation as a new metric of propulsive pattern repeatability and showed cycle velocity variation changes is correlated to the Cauchy index (rx,y = 0.72, P < 0.01). These findings indicate that IdC can be used as a predictor of performance only when swimmers of homogeneous expertise level are studied and suggest the scrutiny of both intra-cyclic velocity variation and cycle velocity variation as a requisite to study the motor adaptations of the swimmer in facing new constraints.